2013
DOI: 10.5539/ies.v6n11p77
|View full text |Cite
|
Sign up to set email alerts
|

Unethical Behavior of the Students of the Czech University of Life Sciences

Abstract: The cheating can be viewed as a major educational problem with a broad social concern. The unethical behaviour of students can crucially influence their qualification, future employment and manners in their professional carrier. The contribution investigates the unethical behaviour of the students of the University of Life Sciences in Prague. The goal is to examine if the students would act unethically in an examination tests and in proceeding their assignments. The inquiry investigation based on self-assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Highlighted by the authors "effort-free" character of glam-education is confirmed by Domeova and Jindrova. They marked the increase in the number of students different in unethical behavior, who try to reach the best results without own intensive and regular work, to get the graduation with minimum effort (Domeova & Jindrova, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Highlighted by the authors "effort-free" character of glam-education is confirmed by Domeova and Jindrova. They marked the increase in the number of students different in unethical behavior, who try to reach the best results without own intensive and regular work, to get the graduation with minimum effort (Domeova & Jindrova, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Academic misconduct and unethical behavior of students are listed as serious educational problem of broad social concern; students' unethical behavior affects their qualifications and comportment in their future professional career (Dömeová and Jindrová 2013). Plagiarism, in particular, has been widespread within higher education for as long as some records of such academic misconduct have existed (Ison 2014).…”
mentioning
confidence: 99%
“…Dömeová et al, 2011;Vostrá-Vydrová et al, 2012;Jindrová et al, 2013;Dömeová et al, 2013) deal with some courses in the University of Life Sciences in Prague. These studies were based on a self-evaluation of the students expressed in a questionnaire.…”
Section: Continuity With Previous Researchmentioning
confidence: 99%